Comparison of the MHC I Immunopeptidome Repertoire of B‐Cell Lymphoblasts Using Two Isolation Methods. Issue 12 (24th April 2018) - Lanoix, Joël; Durette, Chantal; Courcelles, Mathieu; Cossette, Émilie; Comtois‐Marotte, Simon; Hardy, Marie‐Pierre; Côté, Caroline; Perreault, Claude; Thibault, Pierre
Abstract: Significant technological advances in both affinity chromatography and mass spectrometry have facilitated the identification of peptides associated with the major histocompatibility complex class I (MHC I) molecules, and enabled a greater understanding of the dynamic nature of the immunopeptidome of normal and neoplastic cells. While the isolation of MHC I‐associated peptides (MIPs) typically used mild acid elution (MAE) or immunoprecipitation (IP), limited information currently exists regarding their respective analytical merits. Here, a comparison of these approaches for the isolation of two different B‐cell lymphoblast cell models is presented, and it is reported on the recovery, reproducibility, scalability, and complementarity of identification from each method. Both approaches yielded reproducible datasets for peptide extracts obtained from 2 to 100 million cells, with 2016 to 5093 MIPs, respectively. The IP typically provides up to 6.4‐fold increase in MIPs compared to the MAE. The comprehensiveness of these immunopeptidome analyses is extended using personalized genomic database of B‐cell lymphoblasts, and it is discovered that 0.4% of their respective MIP repertoire harbored nonsynonymous single nucleotide variations (also known as minor histocompatibility antigens, MiHAs).